Genotype‐temperature interactions on larval performance shape population structure in hybridogenetic water frogs (Pelophylax esculentus complex). (24th January 2013) - Pruvost, Nicolas B. M.; Hollinger, Daniel; Reyer, Heinz‐Ulrich; Wilson, Robbie
Summary The evolutionary potential and ecological importance of interspecific hybrids continues to be a controversial issue. Traditionally, hybridization – often associated with polyploidy and clonal reproduction – was considered an important mechanism for speciation in plants, but not in animals. More recently, investigations have shifted to the question: Under which genetic and ecological conditions do hybrid taxa and different ploidies arise and succeed, and when and where do they fail? Finding answers to this question is aggravated by the fact that suitable taxa for such studies are often far apart on the phylogenetic tree. Hence, results are influenced by many confounding variables. In this study, we reduce this problem by investigating the fitness within a complex of three closely related water frog taxa consisting of the two sexually reproducing parental species Pelophylax lessonae (genotype LL) and P. ridibundus (RR) plus their interspecific hybrid P. esculentus which comes in three ploidy types (LR, LLR and LRR), as well as with sexual and hemiclonal reproduction. Offspring of all five genotypes were produced by artificially crossing adults sampled from populations in Slovakia, Germany and Switzerland. This created genetic variation. They were then raised at two temperature levels: 18 and 24 °C. This created ecological variation. Larval performance under the two temperature regimes was analysed with respect to three fitness‐related parameters: survival rate, days to metamorphosis and weight at tail resorption. Survival rate was significantly higher for offspring of the three hybrid types (LR, LLR and LRR) compared with those of the parental species (LL, RR), at both rearing temperatures. For days to metamorphosis and weight at metamorphosis, we found an interaction between offspring type and temperature. In both cases, performance of hybrid and parental offspring did not differ at 24 °C, but at 18 °C hybrids metamorphosed faster and at a lower weight than parentals. We discuss these results in relation to those from other studies and conclude that under cold conditions hybrids (especially the two triploid types) have higher fitness than both parental species. This genotype × environment interaction could be one reason why all‐hybrid populations mainly occur at the cooler northern range of the water frog distribution.